Upiór opery Gastona Leroux jako opowieść o wykluczeniu – interpretacja w perspektywie hermeneutycznej - Żulińska, Marta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
The subject of this article is an analysis of the social exclusion of the main character of The Phantom of the Opera by Gaston Leroux – Erik, a brilliant, deformed, isolated composer living in the vaults of the Paris Opera. The structure of the text is determined by a reconstruction of the man’s story and an interpretation of the mechanisms of his exclusion. I consider whether the character’s fate was determined and whether (and to what extent) Erik is to blame for his situation. I base my analysis on classical hermeneutics, which emphasises above all the context in which the novel was written and its ideological significance, although social science issues (especially sociology and psychology) remain equally important. I also refer to the pseudo-sciences still popular in the early 20th century: physiognomy and phrenology.
Gaston Leroux’s The Phantom of the Opera as a story about social exclusion – a hermeneutic interpretation
Keywords: depersonalisation; Gaston Leroux; stigmatisation; The Phantom of the Opera